Problematika Adaptasi Pendekatan Deep Learning Dalam Pembelajaran Matematika Di Indonesia : Jurnal Penelitian Matematika dan Pendidikan Matematika - Dhelinda Nuriatul Ainie; Muhammad Alfaf Aghnia Muthmain; Ida Nuraida; Wati Susilawati (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
The digital transformation in education has encouraged the integration of artificial intelligence technologies, including the deep learning approach in mathematics learning. This study aims to identify the challenges in adapting deep learning in Indonesia through a Systematic Literature Review (SLR) method. The findings indicate that while this approach offers great potential for enhancing personalization and effectiveness in mathematics education, its implementation is hindered by limited infrastructure, low teacher competency in technology, and resistance to innovative methods. The study also reveals that institutional readiness and teacher training are crucial for successful implementation. Therefore, a contextual, gradual, and collaborative adaptation model is needed to optimize the integration of deep learning into mathematics education in Indonesia